Public transport pricing: An evaluation of the 9-Euro Ticket and an alternative policy proposal - Mark Andreas Andor; Fabian Dehos; Kenneth Gillingham; Sven Hansteen; Lukas Tomberg (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
The pricing of public transportation is a frequently debated subject, and a notable current trend is leaning towards flat-rate pricing. In the previous year, Germany introduced a flat-rate ticket, enabling individuals to access public transportation across the entire country for just 9 euros per month during the months of June through August. In this paper, we first examine the extent to which the 9-Euro Ticket policy was able to induce a shift from cars to public transport. To this end, we evaluate the policy's impact on mobility behavior and emissions, and compare our results with other analyses of the policy that use different empirical approaches. The combined evidence shows that the flat-rate access induced only a marginal shift from car to public transport. The 9-Euro Ticket has primarily been used to expand personal mobility rather than to substitute between modes of transportation. In a further step, we subject the 9-Euro Ticket to a cost-benefit analysis based on its achieved carbon reduction. When compared to other climate policies, the costs appear disproportionately high. We use these results as a starting point to discuss flat-rate pricing for public transport in conjunction with evidence from programs in other European cities and insights from economic theory. Synthesizing the collected sources, we conclude that there are better options. Instead of a flat-rate ticket, we call for a cheap and dynamic public fare system that prices peak times higher than off-peak times to avoid overcrowding during peak hours. At the same time, a dynamic road pricing system should be introduced. This would further reduce the negative externalities of driving, generate revenues to support public transport, and provide a stronger incentive to switch from car to public transport.
Keywords: R48; Q48; Q51; 330; Public transport; dynamic pricing; congestion charging; road pricing; flat-rate tariffs; 9-Euro ticket